Hemokultúra levételének helyes metodikája. - Csaba, BÁLINT; Annamária, PAKAI; Kinga, Habil GRÓF; Anna, AHMANN Mercédesz; Zsófia, VERZÁR (Nővér, 2021)
Various bloodstream infections are associated with high mortality, so early diagnosis is very important to reduce complications, with the gold standard procedure being blood culture and evaluation. Several databases were used to search for qualitative, relevant literatures (MEDLINE, PubMed, Ebsco). We selected national and international literature on the correct sampling of blood culture and sampling errors published between 2010 and 2020. The timing, method and location of blood culture sampling, the amount and frequency of sampling, the choice of haemoculture bottles, their storage and transport are all factors that influence the outcome. The choice of time can be independent of the clinical condition of the patient. Intravascular cannulation should be avoided if possible. Careful disinfection prior to haemoculture sampling and the use of chlorhexidine disinfection, which is already customary abroad, with the appropriate contact time, will both reduce contamination samples . Whether or not the patient is on antibiotic therapy is a key factor in the choice of blood culture bottle. To ensure optimal detection of pathogens, a quality control phase should be built into the pre-analytical processes . The solution to reduce the number of contaminated samples is to use sampling kits and to follow a mandatory blood culture sampling protocol.